Pola Asuh Orang Tua dan Tingkat Percaya Diri Mahasiswa Stikes di Surabaya - Lestarina, Ni Nyoman Wahyu; Purwantini, Dwi; Wiguna, yunita (Universitas Malahayati, 2024)
ABSTRACT Good parenting is seen as providing a welcoming and friendly environment so that children have high self-confidence. The purpose of this research is to see the relationship between parenting styles and the level of self-confidence of STIKES students in Surabaya. The research design used is a correlational study with a cross-sectional approach. The variables in this research are parents' parenting style and level of self-confidence. The number of respondents for this research was 138 STIKES students in Surabaya who were taken using purposive sampling techniques. The measuring tools used are the Parental Authority Questionnaire (PAQ) and a self-confidence questionnaire. The statistical test used is the Spearman Rank (Rho) correlation test. As many as 80% of parents have a democratic parenting style, and as many as 69% of students have a moderate level of self-confidence. The results of statistical tests obtained a p-value of 0.002, which means there is a relationship between parental parenting and students' level of self-confidence. Parental parenting style has a major contribution to teenagers' self-confidence. There is a need for education regarding the implementation of effective parenting patterns for parents and character education for students so that it can help increase self-confidence. Keywords: Parenting Style, Self-Confidence, Students ABSTRAK Pola asuh orang tua berpengaruh terhadap rasa percaya diri anak. Lingkungan keluarga yang bersahabat dan ramah dapat meningkatkan interaksi antara anak dan orang tua sehingga dapat mengoptimalkan tumbuh kembang anak. Penelitian ini bertujuan untuk melihat hubungan antara pola asuh orang tua dan Tingkat percaya diri mahasiswa STIKES di Surabaya. Penelitian ini menggunakan studi korelasi dengan pendekatan cross sectional. Variabel dalam penelitian ini adalah pola asuh orang tua dan tingkat percaya diri. Jumlah responden penelitian ini sebanyak 138 mahasiswa STIKES di Surabaya yang diambil dengan teknik purposive sampling. Alat ukur yang digunakan adalah Parental Authority Questionnaire (PAQ) serta kuesioner percaya diri. Uji statistik yang digunakan adalah uji korelasi Spearman Rank (Rho). Didapatkan 80% memiliki pola asuh demokratis, sebanyak 69% mahasiswa memiliki tingkat percaya diri yang sedang, Hasil uji statistik didapatkan nilai p 0,002 yang menandakan bahwa ada hubungan antara pola asuh dan tingkat percaya diri mahasiswa. Pola asuh orang tua berkontribusi besar terhadap rasa percaya diri remaja. Perlu adanya edukasi terkait penerapan pola asuh yang efektif pada orang tua serta pendidikan karakter mahasiswa sehingga dapat membantu untuk meningkatkan rasa percaya diri. Kata Kunci: Pola Asuh, Percaya Diri, Mahasiswa